Selbstbestimmung und Verantwortung in der letzten Phase des Lebens - Mieth, Dietmar (European Journal of Mental Health, 2009)
Self-Determination and Responsibility in the Final Stage of Life: The way we think about dying is mostly dependant on our experiences and concepts. In addition to this, passing away is frequently considered the most personal thing in the world. This nearly always reflects protest against some kind of a situation experienced first hand or related by others, which lacked quality of life and quality of death. Once self-determination made a stellar career in medicine, and rightly so, as opposed to foreign decisions made by doctors and nurses, some attempted luring it past this goal. Therefore, some feel safe while caring for sick people and those requiring treatment if they can prove they are acting on express agreement or rejection. With an increase of distrust, the need to take measures against it also increases. Many benefits accrue from selfdetermination. But as in traffic, this right of way requires one to be circumspect, and to consider others. It is one thing to be able to decide about ourselves, and an entirely different thing to set up rules regarding how everybody else should decide. It escapes the attention of many that passing legislation about the freedom of care, treatment and accompaniment to death is not only about an existential point of view, but also the shared responsibility of society. Those, who regard self-determination only as an unopposed choice, which all other concerned parties need to subject their responsibility to, ignore the fact that responsible self-determination always needs to take others into consideration. Responsibility is, at the same time, an obligation to ourselves. Those who see they are a burden to others and remain isolated will lose some of the meaning they give to life. Self-determination often becomes the focus of discussion when money becomes scarce, and people no longer feel they have time for those requiring care. What they are left with is often – improperly – called ‘self-determination’. Responsibility means seeing people in relationships that do not treat everything individually. This is precisely why we have a civic responsibility to ensure that people do not remain on their own and receive help in carrying their burden once their life becomes restricted. In this case we not only honour their selfdetermination to save ourselves some responsibility, but rather to give them respect.